Environmental literacy profiles: High school student perspectives in Tawau Sabah - Ahmadi Abd Wahab; Mohammad Tahir Mapa (GEOGRAFIA Online, 2020)
Environmental literacy (LAS) is the aim of the Environmental Education (PAS) curriculum. Whereas developing environmentally responsible behavior is the ultimate goal of PAS. Since the Declaration of Tbilisi (1977), PAS in Malaysia is still being implemented in schools across the curriculum. After 42 years of the declaration, there is a need for comprehensive research to provide data on the level of environmental literacy of students in Malaysia. It is important to evaluate the effectiveness of PAS practices and to evaluate the achievement of the goals of shaping environmentally responsible behavior among students. Therefore, this study was conducted to evaluate the environmental literacy profiles (domains and components) of students by gender. Levels of students' environmental literacy profiles by domain and gender were also assessed in this study. Finally, an assessment of the overall level of environmental literacy of high school students in Tawau, Sabah, was also reported. The study was conducted using a Cross-Sectional Survey. The respondents of the study involved 12 urban secondary schools. A total of 328 forms four students were selected on a random sampling basis. Data were collected using questionnaire form and analyzed using ttest, Mann-Whitney U and mean scores. The results showed that affective and environmental behavior profile of male students was higher than female students. Meanwhile, the proficiency component profile involved and environmental problem solving skills were higher than that of female students. Male students were also found to have higher levels of environmental literacy than female students. The environmental skills domain recorded the highest mean score value. Thus, the domain of environmental behavior recorded the lowest score. Overall, the mean score value for environmental literacy among students was moderate. Therefore, to achieve the ultimate goal of environmental education to develop environmentally responsible behavior, environmental education at the school level needs to be strengthened.